Political Islam essays from Middle East report - Beinin, Joel, 1948-; Stork, Joe (I.B. Tauris, 1997)
Bringing together articles and writing on political Islam, this work challenges generalizations about what the Western media and political establishments call "Islamic fundamentalism" and shows the complexity of these movements. Issues covered include gender relations and popular culture.